New store specializes in catalog return items (Raton, NM Raton Range, 1994)
This article is about the Dona Ana Plaza expanding by adding the Catalog Return Store.
Newspaper article
Master list item #: 55
File location is in the Raton file Cabinet
Keywords: Caldwell, Bill; Caldwell, Eva; Chambers, Warren; Chambers, LaVerne; Dona Ana Plaza; Catalog Return Store; Retail Stores; Local Business; Merchandise; Store Openings; Raton, New Mexico